ARGUMENTASI HUKUM PADA VONIS PUTUSAN BEBAS TERHADAP PELAKU PEMBUNUHAN (STUDI PUTUSAN NOMOR 454/PID.B/2024/PN SBY) - Sifanny Nurhaliza; Yana Indawati (Journal Publicuho, 2025)
The acquittal of murder perpetrators often causes controversy in the criminal justice system. This research analyses the legal arguments in Decision Number 454/Pid.B/2024/PN Sby, which acquitted the defendant of all charges despite strong evidence, including witness testimony, post-mortem results, and CCTV footage. The research method used is normative legal research with statutory, case, and conceptual approaches. The results showed that the judge's consideration in the formal law aspect was less careful in assessing the evidence that had met the criteria of Article 184 of the Criminal Procedure Code, thus ignoring substantive justice. From the material law aspect, the judge did not consider the element of dolus eventualis in Article 338 of the Criminal Code and the element of negligence in Article 351 paragraph (3) of the Criminal Code, even though the defendant's actions showed a clear causal relationship with the death of the victim. This decision has the potential to create a bad precedent in the Indonesian criminal justice system and create public distrust of the legal system. Therefore, further scrutiny of similar verdicts is needed to ensure justice for victims and maintain the integrity of the judiciary.